2021
DOI: 10.1111/gcb.15645
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the effectiveness of national commitments to protected area expansion for conserving biodiversity and ecosystem carbon under climate change

Abstract: Global commitments to protected area expansion should prioritize opportunities to protect climate refugia and ecosystems which store high levels of irrecoverable carbon, as key components of an effective response to biodiversity loss and climate change. The United States and Canada are responsible for one‐sixth of global greenhouse gas emissions but hold extensive natural ecosystems that store globally significant above‐ and below‐ground carbon. Canada has initiated a process of protected area network expansio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 102 publications
2
43
0
Order By: Relevance
“…The 2015 planning process for conservation of the greater sage grouse (Centrocercus urophasianus), which resulted in new protections on 67,000 km 2 of habitat "strongholds" in 10 western states (Pidot, 2018), and the Desert Renewable Energy Conservation Plan (DRECP), which coordinated biodiversity conservation in in California's southeastern desert with expansion of solar, wind, and geothermal infrastructure (Kreitler et al, 2015), were subsequently weakened by the Trump administration's focus on resource development. However, with political resolve, new efforts could employ similar templates to advance regional and landscape-level conservation planning, including that designed to achieve ecosystem-based carbon mitigation goals, while at the same time efficiently protecting individual species facing extinction (Carroll and Ray, 2021). President Biden took one such step in 2022, issuing an executive order requiring the U.S. Forest Service and Bureau of Land Management to inventory mature and old-growth forests on federal land and develop "climate-smart management and conservation strategies" to address threats to those forest ecosystems (White House, 2022).…”
Section: Ensuring Coherence Between Element and Spatial Targets In Us...mentioning
confidence: 99%
See 2 more Smart Citations
“…The 2015 planning process for conservation of the greater sage grouse (Centrocercus urophasianus), which resulted in new protections on 67,000 km 2 of habitat "strongholds" in 10 western states (Pidot, 2018), and the Desert Renewable Energy Conservation Plan (DRECP), which coordinated biodiversity conservation in in California's southeastern desert with expansion of solar, wind, and geothermal infrastructure (Kreitler et al, 2015), were subsequently weakened by the Trump administration's focus on resource development. However, with political resolve, new efforts could employ similar templates to advance regional and landscape-level conservation planning, including that designed to achieve ecosystem-based carbon mitigation goals, while at the same time efficiently protecting individual species facing extinction (Carroll and Ray, 2021). President Biden took one such step in 2022, issuing an executive order requiring the U.S. Forest Service and Bureau of Land Management to inventory mature and old-growth forests on federal land and develop "climate-smart management and conservation strategies" to address threats to those forest ecosystems (White House, 2022).…”
Section: Ensuring Coherence Between Element and Spatial Targets In Us...mentioning
confidence: 99%
“…Although these commitments are strongly stated, it is not yet clear how they will be achieved, especially given that the Biodiversity Strategy for 2020 target to restore at least 15% of degraded ecosystems has had limited success (Cortina-Segarra et al, 2021). Coordinated and binding measures must be taken by the EU to ensure that Member States successfully contribute to meeting ambitious restoration targets, which should also be coordinated with ecosystem-based climate mitigation efforts (Carroll and Noss, 2020;Carroll and Ray, 2021).…”
Section: Ensuring An Ambitious Nature-positive Approach In Us and Eu ...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, some challenges exist. First, a growing body of available spatial data for identifying areas important for climate adaptation means that planners must reconcile a diversity of data (Carroll and Ray 2021). Previous research indicates that identified priority areas can be highly dependent on the datasets used as each represents different mechanisms and highlights different landscapes (Michalak et al 2020, Carroll andRay 2021).…”
Section: Introductionmentioning
confidence: 99%
“…First, a growing body of available spatial data for identifying areas important for climate adaptation means that planners must reconcile a diversity of data (Carroll and Ray 2021). Previous research indicates that identified priority areas can be highly dependent on the datasets used as each represents different mechanisms and highlights different landscapes (Michalak et al 2020, Carroll andRay 2021). Second, the majority of prioritization frameworks for protected areas expansion focus on current spatial patterns in biodiversity, landscape connectivity and other key factors (Cushman et al 2009, Lookingbill et al 2010, Dickson et al 2013, Belote et al 2016.…”
Section: Introductionmentioning
confidence: 99%